2018
DOI: 10.1111/codi.13906
|View full text |Cite
|
Sign up to set email alerts
|

Denonvilliers’ fascia in men: a sheet plastination and confocal microscopy study of the prerectal space and the presence of an optimal anterior plane when mobilizing the rectum for cancer

Abstract: Aim The aim of this study was to investigate the detailed, in situ, morphology of Denonvilliers’ fascia (DVF) in cadavers using sheet plastination and confocal microscopy and to review and describe the optimal anterior plane for mobilization of the distal rectum. Method Six male cadavers (age range 46–87 years) were prepared as six sets of transverse (× 2), coronal (× 1) and sagittal (× 3) plastinated sections which were examined under a confocal laser scanning microscope. Results In this study a consistent sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…The lateral part of the fascia lata overlapped the sartorius and was formed by 2-3 curtain strip-like ligaments which were termed "the iliolata ligaments" in this study ( Fig. 2A,B) 18 . The iliolata ligaments Fascia-like structures underneath the fascia lata.…”
Section: Resultsmentioning
confidence: 74%
“…The lateral part of the fascia lata overlapped the sartorius and was formed by 2-3 curtain strip-like ligaments which were termed "the iliolata ligaments" in this study ( Fig. 2A,B) 18 . The iliolata ligaments Fascia-like structures underneath the fascia lata.…”
Section: Resultsmentioning
confidence: 74%
“…Furthermore, from a technical point of view, we would suggest that a key issue in this debate remains as to how best to identify the correct plane of mobilization at operation whether the procedure be performed by open surgery or by a combined laparoscopic and robotic approach and especially when attempting to resect the rectum by a transanal TME technique. A recent study revealed the precise nature, fine architecture, and localization of membrane-like structures present within the prerectal space and confirmed that the optimal plane for the anterolateral mobilization of the rectum is posterior to the multilayered DVF (Xu et al, 2018). Thus, we agree with the authors' description that to identify the correct anterior plane, the dissection must commence precisely in line with the peritoneal reflection from the back of the prostate or vagina to ensure identifying the correct avascular plane posterior to DVF (Bokey, 2013).…”
mentioning
confidence: 79%
“…More recently, plastination has been introduced for long term preservation of tissues, organs, systems and whole body by replacement of water and lipid with plastic monomers which impart transparency to the objects [17]. Plastination was rather suitable for establishing educational materials than used for biomedical research in histopathology due to its penetrating limitation less than 3 mm of thickness after plastic polymerization [18][19][20] [70,71] Abbreviations: FLIM, fluorescence lifetime imaging; ADOTA, azadioxatriangulenium; LED, light emitting diode. [38].…”
Section: History Of Tissue Clearingmentioning
confidence: 99%